PENGGUNAAN ANTCONC DALAM ANALISIS MAKNA KUKURU’U DAN LU’U SEBAGAI PADANAN STAY AT HOME DALAM BAHASA MELAYU KUPANG The Use Antconc in Analyzing The Meaning of 'Kukuru'u' and 'Lu'u' as The Translation of 'Stay at Home' in Kupang Malay Language - Leo, Haniva Yunita (Jurnal Lingko : Jurnal Kebahasaan dan Kesastraan, 2020)
AbstrakSelama pandemi Covid-19, anjuran untuk stay at home mulai dikampanyekan melalui berbagai media. Frasa tersebut kemudian dipadankan dalam bahasa daerah dengan tujuan keefektifan penyampaian informasi. Dalam bahasa Melayu Kupang, stay at home dipadankan dengan dua frasa; kukuru’u di rumah dan lu’u di rumah. Kajian ini bertujuan untuk menganalisis makna kata kukuru’u dan lu’u untuk mencari padanan yang lebih tepat dengan menggunakan metode analisis korpus. Korpus bahasa Melayu Kupang kemudian dianalisis menggunakan AntConc untuk membandingkan kolokasi kedua kata yang berdekatan makna (near-synonyms). Hasil analisis korpus menunjukkan bahwa kukuru’u lebih banyak berkolokasi dengan aktivitas di dalam rumah, sedangkan lu’u mengandung konotasi negatif dan merupakan aktivitas yang tidak hanya berlangsung di dalam rumah. Dengan demikian, kukuru’u dapat digunakan sebagai padanan yang lebih tepat untuk anjuran stay at home.Kata-kata kunci: Kukuru’u, Lu’u, Analisis Korpus, AntConc, Sinonim, Bahasa Melayu KupangAbstractDuring Covid-19 pandemic, people have been suggested to stay at home, resulting in the campaign of ‘stay at home’ in various types of media. For the sake of communication effectiveness, the phrase has been translated into local languages, one of which is Kupang Malay Language. In Kupang Malay Language, ‘stay at home’ is translated into two phrases, namely ‘kukuru’u di rumah’ and ‘lu’u di rumah’. This paper is aimed at analysing the meaning of ‘kukuru’u’ and ‘lu’u’ in order to find the most appropriate equivalence by using corpus analysis method. The corpus of Kupang Malay Language was analysed using AntConc to compare the collocation of the two near-synonyms. The result of corpus analysis indicated that kukuru’u is mostly collocated with activities in house, while lu’u has a negative connotation and is related to activities conducted not only at home but outside home as well. Thus, kukuru’u is suggested as the most suitable equivalence of ‘stay at home’.Keywords: Kukuru’u, Lu’u, Corpus Analysis, AntConc, Near-synonyms, Kupang Malay Language. Abstract During Covid-19 pandemic, people have been suggested to stay at home, resulting in the campaign of ‘stay at home’ in various types of media. For the sake of communication effectiveness, the phrase has been translated into local languages, one of which is Kupang Malay Language. In Kupang Malay Language, ‘stay at home’ is translated into two phrases, namely ‘kukuru’u di rumah’ and ‘lu’u di rumah’. This paper is aimed at analysing the meaning of ‘kukuru’u’ and ‘lu’u’ in order to find the most appropriate equivalence by using corpus analysis method. The corpus of Kupang Malay Language was analysed using AntConc to compare the collocation of the two near-synonyms. The result of corpus analysis indicated that kukuru’u is mostly collocated with activities in house, while lu’u has a negative connotation and is related to activities conducted not only at home but outside home as well. Thus, kukuru’u is suggested as the most suitable equivalence of ‘stay at home’.